Encounters between the dominant health system and other health systems in Peru (2000-2012) - Velásquez, Tesania (2018)
In Peru, health is understood in different ways and there are many practices that seek to maintain it. Each of these responds to spaces of identity and meaning shared by a community. While the official discourse promotes a bio-psychosocial model of health, many of the communities historically share different meanings and rituals in relation to health. The aim of this paper is to explore the encounters and misunderstandings between the official health system and other health systems during the first decade of 21st. century. To this end, a community approach is proposed, which exposes the historical and political characteristics that deny the recognition of other knowledge. The discussion focuses on the internal armed conflict and the Final report of the Truth and Reconciliation Commission (CVR).